Functional Memristors: Optically Modulated Threshold Switching in Core–Shell Quantum Dot Based Memristive Device (Adv. Funct. Mater. 16/2020). (20th April 2020) - Wang, Junjie; Lv, Ziyu; Xing, Xuechao; Li, Xiaoguang; Wang, Yan; Chen, Meng; Pang, Guijian; Qian, Fangsheng; Zhou, Ye; Han, Su‐Ting
Abstract : In article number 1909114, Ye Zhou, Su‐Ting Han, and co‐workers present a photonic memristor featuring UV‐sensitive quantum dot‐based switching media. The memristive device can be readily switched from the nonvolatile to volatile threshold regime via UV light, providing a noninvasive method for storing data in both a temporal and permanent manner in a single device.